2013
DOI: 10.2341/11-494-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operator Experience on the Outcome of Fiber Post Cementation With Different Resin Cements

Abstract: RelyX U100 (commercially available outside Brazil as RelyX Unicem) was shown not to be affected by the operator's experience and therefore seems to be more suitable for use by less experienced clinicians. Materials and Methods: The roots of 48 extracted human maxillary central incisors were prepared and divided into six groups (n=8), according to combination of the above factors. Glass fiber posts were cemented in accordance with the instructions of the manufacturer of each cementation system. After water stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 24 publications
2
21
0
8
Order By: Relevance
“…From the 34 studies included, 14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47 35 distinct data sets were extracted because one article had two different data sets. 23 BS values are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 34 studies included, 14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47 35 distinct data sets were extracted because one article had two different data sets. 23 BS values are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the regression model divided according to resin cement type show that post retention following the use of regular resin cements is more greatly influenced by the variables, suggesting that self-adhesive resin cements are less technique-sensitive. A recent study 37 showed that, in contrast to regular resin cements, the performance of self-adhesive resin cements for luting GFPs was not influenced by operator experience. Nevertheless, for regular cements, luting the post without applying cement around it outperformed luting the post and applying cement around it.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between any adhesive protocols evaluated, while the null hypothesis tested was accepted. Other studies evaluating cementation of fiber posts have also found similarity of bond strength between self-adhesive cements and multiple-step protocols [14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…34 Moreover, the inclusion of multiple steps increases technique sensitivity. 35 Nonetheless, some authors have found no significant differences in the bond strength in different parts of the root canal. 36,37 Another aspect that can influence the bond strength is the depth of light penetration.…”
Section: Discussionmentioning
confidence: 99%